The Impact of Hearing Loss and Hearing Aid Usage on the Visuospatial Abilities of Older Adults in a Cohort of Combined Hearing and Cognitive Impairment - Utoomprurkporn, Nattawan; Stott, Joshua; Costafreda, Sergi; Bamiou, Doris-Eva (Frontiers in Aging Neuroscience, 2022)
Abstract Introduction: It has been proposed that hearing loss may result in improved visuospatial abilities. The evidence for this assertion is inconsistent, and limited to studies in congenitally deaf children, despite older adults with age-related hearing loss constituting the vast majority of the hearing impaired population. We assessed visuospatial (visuoconstruction and visuospatial memory) ability in older adult hearing aid users with and without clinically significant cognitive impairment. The primary aim of the study was to determine the effect of hearing loss on visuospatial abilities. Method: Seventy-five adult hearing aid users (HA) aged over 65 were recruited, out of whom 30 had normal cognition (NC-HA), 30 had mild cognitive impairment (MCI-HA) and 15 had dementia (D-HA). The Rey Osterrieth Complex figure test (ROCFT) copy, 3 minutes recall and 30 minutes recall tests were performed to evaluate the visuoconstructional and visuospatial memory abilities of the participants. Result: There were significant differences between the ROCFT copy, 3 mins recall, and 30 minutes recall among the three cohorts (p<0.005). Compared with previously published normative data, the NC-HA performed significantly better in the ROCFT copy (p<0.001), immediate recall (p<0.001) and delay recall (p=0.001), while the MCI-HA performed similarly to the expected norms derived from population (p=0.426, p=0.611, p=0.697 respectively), and the D-HA performed below this norm. Conclusion: Though visuospatial abilities tend to decline when the global cognitive functioning declines, We found suggestive evidence for positive effects of age-related hearing loss on visuospatial cognitive ability. Participants with mild cognitive impairment and hearing loss, who would have been expected to perform worse than normative data, were in fact performing as well as cognitively healthy subjects without hearing loss. Visuospatial ability could be targeted when providing rehabilitation for the older adults with hearing loss